The novel anti-neuroinflammatory functional food CCL01, a mixture of Cuscuta seed extracts and Lactobacillus paracasei NK112. Issue 14 (23rd June 2022) - Hong, Seong Min; Ju, In Gyoung; Kim, Jin Hee; Park, Sang Cheol; Choi, Jin Gyu; Sohn, Mi Won; Oh, Myung Sook; Kim, Sun Yeou
Abstract : The medical herbal mixture (CCL01) including Cuscuta seeds and Lactobacillus paracasei NK112 has inhibitory effect on LPS-induced microglial inflammation and may be a potential functional food for neuroinflammation-related diseases. Abstract : Neuroinflammation, which occurs due to microglia, is related to the pathogenesis of neurodegenerative disorders. Recently, the development of functional foods that down-regulate over-activated microglial cells to prevent the progression of neurodegenerative disorders has been proposed, since over-activated microglia induce a chronic source of neurotoxic factors and reduce neuronal survival. Thus, the anti-neuroinflammatory effects of a functional food mixture (CCL01) including Cuscuta seeds and Lactobacillus paracasei NK112 on lipopolysaccharide (LPS)-induced experimental models were investigated. In LPS-induced in vitro models, the expression levels of inflammatory mediators ( e.g., inducible nitric oxide synthase, cyclooxygenase-2, nitric oxide, and prostaglandin E2) and pro-inflammatory cytokines ( e.g., tumor necrosis factor-α, interleukin (IL)-1β, and IL-6) were decreased upon CCL01 treatment. CCL01 showed an anti-neuroinflammatory effect in LPS-induced microglial cells via the inhibition of the mitogen-activated protein kinase (MAPK)/nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway and the activation of the nuclear factor erythroid-2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) pathway. In the LPS-treated in vivo mouse models, the increased expression of ionized calcium binding adaptor molecule 1 (Iba-1), which indicates microglial activity, was markedly decreased upon treatment with CCL01 (50 and 200 mg kg −1 ) in the hippocampus and cortex areas of the mouse brains in comparison with the LPS-injected group. In addition, the groups to which CCL01 was administered had significantly decreased plasma levels of tumor necrosis factor-α, interleukin (IL)-1β, and IL-6 in the LPS-injected mouse models. Our data suggest that CCL01 may be a potential anti-neuroinflammatory agent that can prevent microglia overactivation, and it could be useful for developing functional foods.